Wacana Tata Kelola Kebencanaan: Kajian Pembicaraan Aktor Melalui Analisis Media Sosial Twitter - Sapto Setyo Nugroho; Daniel Pasaribu (Universitas Terbuka, 2022)
This paper examines the discourse on disaster governance issues in Indonesia. By focusing on discourse analysis, disaster studies can be viewed with a social science perspective and with a discursive governance approach. This paper is also an alternative to the dominant concept of